Development of the model of the proactive approach in creation of distributed information systems - Morozov, Viktor; Kalnichenko, Elena; Bronin, Sergiy (Eastern-European Journal of Enterprise Technologies, 2018)
We discuss an integrated approach to complex projects management, creating distributed information systems, which is based on the analysis of the relationship of project management processes, product creation, management of interested parties and external environment. We analyzed the features of project implementation on the development of distributed information systems that are subject to the significant number of complex effects from the turbulent external environment and project response to these effects. To solve the resulting problems, a proactive approach was proposed. The work has identified and formalized basic structural elements of models of complex projects of creation of distributed information systems. A conceptual model was built, which facilitated research of the effect of the turbulent environment of the project on all elements of the model. The key branches of knowledge of this effect are identified. We developed the structural model of components in distributed information systems using cloud technologies and design approach, which takes into account the response to dynamic changes and turbulence of the external environment. The mathematical model of the process of creating a complex IT product is constructed, taking into account the influence of the turbulent external environment of the project, the main characteristics and parameters are determined. We performed the modeling of objective functions of the mathematical model of the process of creating a complex IT product. The algorithm of change management based on the proactive approach in the projects of creating distributed information systems is proposed, taking into account monitoring of the project implementation environment and identification of three types of possible events. The studies confirmed the effectiveness of using a proactive approach in projects of creation of distributed information systems, which will allow using the proposed model for managing complex IT projects.